Age-related Increase in Incidence of Postoperative Atrial Fibrillation Following Coronary Artery Bypass Grafting (CABG) Surgery: Incidence of Postoperative Atrial Fibrillation - Ahmed , Salman; Tanveer, Riffat; Sharfi , Masroor; Ali Khahro, Adnan; Lakhani , Shakir; Khan, Asadullah (Pakistan Journal of Health Sciences, 2023)
Atrial Fibrillation (AF) is one of the common arrhythmias after coronary artery bypass grafting (CABG) mostly occurs within 2 to 4 days. The advanced age is one of the important risk factors. Objective: To determine the frequency of Postoperative Atrial Fibrillation (POAF) in patients age between 30-65 years who underwent elective CABG Surgery. Methods: One hundred and thirty-seven Adult patients of either sex between age of 30 to 65 years with three vessel coronary artery disease underwent elective CABG surgery were included in our study. It was descriptive cross-sectional study, conducted at Tabba Heart Institute, Karachi, from December 2021 to June 2022. Postoperatively daily EKG was performed for the evidence of POAF. Results: One hundred and thirty-seven patients, between age group of 30-65 years among them 115 (84%) were male & 22 (16%) were females with mean age of patients 55.91years were included in our study. Post-Operative Atrial Fibrillation (POAF) was observed in 12.4%, out of whom 76.5% were male while 23.5% were female. The mean day of onset of POAF was 2.38 days. The relationship between increasing age groups and AF was found to be statistically significant i.e. p-value 0.04. There is significant difference between age groups and maximum incidence of POAF were found in above 60 years. Conclusions: In our study frequency of POAF was found in 12.4 %with mean age of participants was found to be 55.91 ± 6.5 years. Objective: To determine the frequency of Postoperative Atrial Fibrillation (POAF) in patients age between 30-65 years who underwent elective CABG Surgery. Methodology: One hundred and thirty seven Adult patients of either sex between age of 30 to 65 years with three vessel coronary artery disease underwent elective CABG surgery were included in our study. It was descriptive cross-sectional study, conducted at Tabba Heart Institute, Karachi, from December 2021 to June 2022. Postoperatively daily EKG was performed for the evidence of POAF. RESULT: One hundred and thirty seven patients, between age group of 30-65 years among them 115 (84%) were male & 22 (16%) were females with mean age of patients 55.91years were included in our study. Post-Operative Atrial Fibrillation (POAF) was observed in 12.4%, out of whom 76.5% were male while 23.5% were female. The mean day of onset of POAF was 2.38 days. The relationship between increasing age groups and AF was found to be statistically significant i.e. p-value 0.04. There is significant difference between age groups and maximum incidence of POAF were found in above 60 years. CONCLUSION: In our study frequency of POAF was found in 12.4 %with mean age of participants was found to be 55.91 + 6.5 years.